Slovak Republic : 2011 Article IV Consultation-Staff Report; Informational Annex; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
The Slovak economy showed recovery from sharp recession. Executive Directors suggested that restoring fiscal sustainability and removing unemployment while maintaining external competitiveness within the monetary union should be given priority. The fiscal consolidation strategy could be facilitated by adopting real expenditure growth with deficit targets and expenditure policy priorities, including reforming health care and pensions. However, public procurement and absorption of EU funds are important for enhancing the business environment and strengthening public sector governance.